Centrifuge modeling of geosynthetic-encased stone column-supported embankment over soft clay - Chen, Jian-Feng; Li, Liang-Yong; Zhang, Zhen; Zhang, Xu; Xu, Chao; Rajesh, Sathiyamoorthy; Feng, Shou-Zhong (Geotextiles and geomembranes, 2021)
Geosynthetic-encased stone column (GESC) has been proven as an effective alternative to reinforcing soft soils. In this paper, a series of centrifuge model tests were conducted to investigate the performance of GESC-supported embankment over soft clay by varying the stiffness of encasement material. The enhancement in the performance of stone columns encased with geosynthetic materials was quantified by comparing the test with ordinary stone columns (OSCs) under identical test conditions. The test results reveal that by encasing stone columns with geosynthetic material, a significant reduction in the ground settlement, relatively faster dissipation of excess pore pressure and enhanced stress concentration ratio was noticed. Moreover, with the increase in the encasement stiffness from 450 kN/m to 3300 kN/m, the stress concentration ratio increased from 4 to 6.5, which signifies the importance of encasement stiffness. In addition, a relatively lower value of soil arching ratio observed for GESCs compared to OSCs indicate the formation of a relatively strong soil arch in the GESC-supported embankment. Interestingly, under embankment loading, GESCs fail by bending while OSCs fail by bulging. The stress reduction method can be used to calculate the settlement of GESC-supported embankment with larger stress reduction factor than that in the OSC-supported embankment. Finally, the limitation of the construction of the embankment at 1 g was addressed.